Health Promoting Behaviour among School Going Adolescents of Government School in Gaidakot, Nawalparasi - Ghimire, Babita; Aryal, Barsha; Upadhyay, Hari Prasad (International Journal of Silkroad Institute of Research and Training, 2024)
Background: A health-promoting behavior is an endpoint or action-outcome directed toward attaining positive health outcomes such as optimal wellbeing, personal fulfillment, and productive living. Adolescents make up as much as a quarter of the population and the number of adolescents is expected to rise through 2050. Adolescents are vulnerable to the risk factors contributing to Noncommunicable diseases, whether from unhealthy diets, physical inactivity, exposure to tobacco smoke or the harmful use of alcohol. Method: A cross sectional analytical study design was used among 89 adolescents of grade 9 and 10 was selected through enumerative sampling technique. Data was collected using a self–administered questionnaire from Adolescent Health Promoting – Short Form scale and entered in excel and analyzed by Statistical Package for Social Science (SPSS) version 20.0 using Descriptive statistics (Frequency, percentage, mean, standard deviation) and interferential statistics (chi-square). Result: Findings revealed that 48.3% respondents obtained below average mean score on health promoting behaviour. The overall mean ± S.D of status of health promoting behaviour was 68.12±8.847. Among 6 subscales, life appreciation obtained the highest mean score (with standard deviation) i.e. 15.35±3.72, whereas exercise obtained least mean score (with standard deviation) i.e. 7.80±2.66 and there is statistically significant association with health promoting behaviours among adolescents and educational status of mother (p=0.033). Conclusion: Overall health promoting behaviours among adolescents is below average so it is necessary to improve in areas like nutrition and exercise. There is significant association between parental education and health promoting behaviours of the adolescents, so parental education should be improved by school committee, should introduce educational session, awareness program, physical activity program and nutrition exhibition program regarding health promoting behaviours since early grade.